Correlation between indicators of hemostasis system activity and antiphospholipid antibodies levels in women with miscarriage - Elena N Kravchenko; Anastasiia A Goncharova (IP Berlin A.V., 2019)
Aim. To study the correlation between the activity indicators of the blood coagulation system and the content of antiphospholipid antibodies in women with miscarriage, depending on the number of reproductive losses. Materials and methods. 137 cards of women with a history of pregnancy termination were analyzed, divided into 2 groups according to the principle of presence/absence of plasmapheresis in the treatment regimen at the stage of pregravid preparation, followed by ranking into 2 subgroups according to the principle of presence/absence of TORCH infection activity. Results. The highest correlation was found for the presence of autoantibodies against cardiolipin with the severity of antiphospholipid syndrome. Antibodies to b2-glyco-protein-1 were the second parameter in the level of correlation with the number of reproductive losses. The negative effect, diagnostic and pathogenetic value, first of all, of IgG is proved in comparison with IgM, IgG to cardiolipin, IgG to annexin V, IgG to cardiolipin and lupus anticoagulant. The main exogenous cause of antibody formation in AFL is an infectious agent. A key endogenous factor in antibody formation is recognized as a violation of endothelial hemostasis. Conclusion. The correlation relationships between the initial level and the dynamics of the content of antiphospholipid antibodies, the number of gestational losses, as well as a number of parameters of the hemostasis system were revealed and interpreted. An independent negative effect on the laboratory parameters of the antiphospholipid syndrome of gestational losses in an amount of more than two was revealed.